Simplified finite difference thermal lattice Boltzmann method - Che Sidik, Nor Azwadi; Takahiko, Tanahashi (World Scientific Publishing, 2008)

(untitled)
In this paper, a well-known finite difference technique is combined with thermal lattice Boltzmann method to solve 2-dimensional incompressible thermal fluid flow problems. A small number of microvelocity components are applied for the calculation of temperature field. The combination of finite difference with lattice Boltzmann method is found to be an efficient and stable approach for the simulation at high Rayleigh number of natural convection in a square cavity.